PENGARUH CURRENT RASIO (CR), DEBT TO EQUITY RASIO (DER), DAN TOTAL ASSET TURNOVER (TATO) TERHADAP RETURN SAHAM PADA PT. INDOCEMENT TUNGGAL PRAKARSA TBK - ANGGREANI, SITI SYARAH; PRATIWI, ALIAH (Universitas Mahasaraswati K. Mataram, 2024)
This study was conducted with the aim of examining the effect of Current Ratio (CR), Debt To Equity Ratio (DER), and Total Asset Turnover (TATO) on Stock Returns at PT Indocement Tunggal Prakarsa Tbk which is listed on the Indonesia Stock Exchange (IDX) for the period 2009 - 2022. The use of data in this study is based on secondary data with quantitative data. The research instrument used to measure this research uses a list of tables in the form of Current Assets, Current Debt, Total Debt, Total Capital, Sales, and Total Assets from the profit and loss financial statements and balance sheets at PT Indocement Tunggal Prakarsa Tbk. The population of this study is the financial statements of PT Indocement Tunggal Prakarsa Tbk for 33 years, namely from 1989-2022. The sample in this study is the financial statements of PT Indocement Tunggal Prakarsa Tbk for 14 years, namely from 2009 to 2022.The sampling technique used in this study is purposive sampling technique. The data collection techniques used in this study are documentation and literature study. The documentation intended in this study is the financial statements of PT Indocement Tunggal Prakarsa Tbk in the form of balance sheet and income statement from 2009 to 2022. The data analysis technique in this study is to use the classic Assumption Test, Multiple Linear Regression Test, t test, and F test.The results showed that partially the Current Ratio (CR) and Total Asset Turnover (TATO) variables had no effect on stock returns, while the Debt To Equity Ratio (DER) variable partially affected stock returns. Simultaneously the variables Current Ratio (CR), Debt To Equity Ratio (DER), and Total Asset Turnover (TATO) affect stock returns